Games with Espionage - Eilon Solan; Leeat Yariv (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
"There is no place where espionage is not possible." -Sun Tzu, The Art of War, approximately 500BC We consider extensive form games in which players decide on their strategies before the start of play and can purchase noisy information about their opponents' decisions concerning future response policies (i.e., spy on their opponents' decisions). This addition to the agent's optimization problem naturally changes the set of subgame perfect equilibria (SPE). For example, in the chain-store model, for sufficiently small costs of espionage, the population of Incumbents splits into a positive fraction that accommodates and a positive fraction that fights. For general 2x2 games in extensive form, the existence of equilibria with espionage turns out to depend on the difference between the Stackelberg equilibrium payoffs and the SPE payoffs. We characterize the set of equilibria with espionage as a sunset of the set of correlated equilibria. Welfare and Pareto properties of such equilibria are also explored.
Keywords: 330; Espionage; subgame perfect equilibria; information; timing